PENGARUH MOTIF PENGGUNA MEDIA SOSIAL TWITTER @GORIAU.COM TERHADAP KEPUASAN FOLLOWERS DALAM MENDAPATKAN INFORMASI DI KOTA PEKANBARU - Sri Rezky Emarwani; Nurjanah " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In fact, humans are social beings, who every day are always activities and connect with others. All activities are conducted aiming to meet the necessities of life. As time progressed, mass communication can be a different shape, it becomes simpler to use an information technology. Of the many sites on the internet one of the many popular sites today is twitter. The researchers chose twitter as an object of research assignment due, twitter is a tool or medium of communicating over the internet that lately is often used as a place for people looking for the latest information, get the relation or merely to advertise its products. That's why the existence of twitter has now become a lifestyle for most people, almost everyone has now have an account on twitter. As does have email, twitter has also become a necessity nowadays. The purpose of this research is to find out whether there is influence of online media use twitter motives against the satisfaction felt by followers on @GoRiauCom account in obtaining information regarding the city of Pekanbaru.The methods used in this study i.e., quantitative methods. Data collection techniques in the study using a detailed questionnaire. The number of samples to study as many as 100 respondents. Withdrawal of samples using a Simple Random Sampling method. To know the influence of both these variables, the researchers used a simple linear regression analysis. For the processing of data is carried out using a questionnaire, the statistical program Product And Service Solution (SPSS) Windows version 18.The results of the research on the influence of social media twitter users motives @goriau. com towards the satisfaction of followers in getting information in the city of pekanbaru regression coefficient values obtained in this study were Y = 13.171 + 0.489 X with a level of significance 0.000 smaller than α = 0.05. This means that there is the influence of social media twitter users motives @goriau. com towards the satisfaction of followers in getting information in the city of pekanbaru 46.50% and enter influencial medium category. The percentage shows that the motive of the use of only most of the factors affecting the satisfaction in getting information on followers social media twitter @GoRiau. com. H0 is rejected and thus Ha is received.Keywords : Communication, Twitter, New Media, Information, Satisfaction